Six cases of seroconversion of human immunodeficient virus (HIV) antibody post-transfusion in HIV seronegative bloods - Chaimongkol B. (2014)
Seroconversion of human immunodeficient virus (HIV)-antibody post blood transfusion has been reported (Jett et al, 1983; Cumming et al, 1989). We report here, six hematologic patients who became HIV-antibody positive after receiving HIV seronegative blood and blood components during their illness. There were three cases of acute non-lymphocytic leukemia, one thalassemia, one dyshemopoiesis and one hemophilia A. Thus, the risk of acquiring HIV infection from transfusion remains, despite the routine serological screening of donated blood by HIV ELISA tests. So the laboratory screening of blood should be improved by using more sensitive and specific antibody kits, including the use of HIV antigen testing, which have been reported to be useful in the diagnosis of patients with the early HIV infection.